Interseeding Cover Crops in Corn. Issue 1 (31st December 2020) - Brooker, Aaron; Renner, Karen
Abstract : Seasonal constraints following corn grain harvest in the upper Midwest often limit cover crop seeding and restrict the species that can establish and produce biomass prior to the winter months. Interseeding cover crops in corn fields in the early vegetative stages of corn is an additional option to establish a cover crop. This article, based on research originally reported in Agronomy Journal (see https://doi.org/10.1002/agj2.20046 ), reports on the results of field experiments in Michigan that evaluated interseeding a number of cover crop species at various corn growth stages. Earn 0.5 CEUs in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/917 .